2015
DOI: 10.1186/s12916-015-0429-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial drugs for preventing malaria during pregnancy and the risk of low birth weight: a systematic review and meta-analysis of randomized and quasi-randomized trials

Abstract: BackgroundIt is known that antimalarial drugs reduce the risk of low birth weight (LBW) in pregnant patients. However, a previous Cochrane review did not evaluate whether the level of antimalarial drug resistance could modify the protective effect of antimalarial drugs in this regard. In addition, no systematic review exists comparing current recommendations for malaria prevention during pregnancy to alternative regimens in Africa. Therefore, we conducted a comprehensive systematic review and meta-analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 55 publications
1
21
1
2
Order By: Relevance
“…Two systematic reviews with 25 (37 981 women) 44 and 17 (14 481 women) 43 RCTs and quasi-RCTs evaluated the effect of antimalarial drugs for preventing malaria during pregnancy and the risk of LBW (see online supplementary table 14). Both reviews found a 27% reduction of LBW for women receiving antimalarial drugs compared with women not receiving these drugs during pregnancy.…”
Section: Preventive Antimalarial Drugsmentioning
confidence: 99%
“…Two systematic reviews with 25 (37 981 women) 44 and 17 (14 481 women) 43 RCTs and quasi-RCTs evaluated the effect of antimalarial drugs for preventing malaria during pregnancy and the risk of LBW (see online supplementary table 14). Both reviews found a 27% reduction of LBW for women receiving antimalarial drugs compared with women not receiving these drugs during pregnancy.…”
Section: Preventive Antimalarial Drugsmentioning
confidence: 99%
“…22 The causes of low birth weight differ between rural, tropical Africa and developed or non-tropical settings: for example, malaria (an important cause of low birth weight) is restricted to the tropics 23 and prophylactic antimalarial drugs in pregnancy reduce the risk of low birth weight. 24,25 We hypothesized that the relationship between birth weight and BP in African settings might differ from that commonly observed in HICs.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also showed that antimalarial drugs appear to be less effective at reducing the risk of LBW in RCTs published before 1996 compared to those published after this period. A potential explanation for this finding is the prevalence of antimalarial drug resistance in those studies that were, on average, 20.32% (median rate of resistance: 21.45%, interquartile range (IQR), 14.7–25.95%), which was above the cut‐off recommended (10%) by the World Health Organization (WHO) for policy change in malaria areas .…”
Section: Discussionmentioning
confidence: 91%